PENGEMBANGAN KOMPETENSI DALAM MENINGKATKAN KINERJA KARYAWAN PADA BAKOEL MOZA DI SUMENEP - Jannah, Nur Fadhilatul; Widyastuti, Endang (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
Employee competencies are still not up to expectations, such as the inability to create and assemble varied and neat handmade items, the price list does not match the sales volume, communication between employees and customers is not yet fully effective, and the employee recruitment SOP is not in place, necessitating competency development. This study aims to determine the description of employee competency development and the obstacles encountered at Bakoel Moza in Sumenep Regency. This type of research uses qualitative methods with observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results show that competency development is carried out through training, division of tasks according to expertise, department transfers, and the creation of a positive work environment. However, the main obstacles are ineffective communication and the lack of comprehensive training. Performance assessments cover discipline, creativity, and responsibility. Competency development strategies have been shown to increase employee productivity and readiness to face work challenges. However, a more systematic approach is needed to ensure all employees develop according to business needs. This study provides an overview of the importance of competency development in improving employee performance at Bakoel Moza.